Strategic Leadership Capabilities and Organizational Agility: Evidence from Emerging Market Firms - Yuniliza; Hery Pratama Putra; Selvi Yona Tamara; Murni Hayati (CV. Get Press Indonesia, 2025)
This study examines Strategic Leadership Capabilities and Organizational Agility: Evidence from Emerging Market Companies. In an era of increasingly dynamic global competition, companies operating in emerging markets face more complex challenges than those in developed markets. Strategic leaders are required not only to have a long-term vision but also to be able to manage change, empower employees, and make future-oriented decisions. The study method uses a Systematic Literature Review (SLR) to review and analyze previous studies relevant to this topic. The results show that strategic leadership and organizational agility have proven to be key pillars in creating long-term competitive advantage for companies in emerging markets. Strategic leadership plays a vital role in projecting vision, managing transformation, and anticipating external threats, while organizational agility provides the adaptive ability to respond quickly to technological changes, consumer shifts, and sudden competitive pressures. This complementary combination where strategic leaders form the foundation of an innovative culture and accelerate decision-making enables organizations to become more agile and responsive, which is ultimately crucial for achieving sustainable success amidst the high complexity and uncertainty of emerging markets.